Low Rate of Intrathecal Baclofen Pump Catheter‐Related Complications: Long‐Term Study in Over 100 Adult Patients Associated With Reinforced Catheter. Issue 7 (11th May 2021) - Feller, Christina N.; Awad, Ahmed J.; Nelson, Mary Elizabeth S.; Ketchum, Nicholas; Pahapill, Peter A.
Abstract: Objectives: Intrathecal baclofen (ITB) is a cost‐effective therapy for patients with severe spasticity. The most common complications are catheter‐related complications (CRCs) including kinking/occlusion, blockage, migration, fracture, disconnection, and CSF leak. Our objective was to determine the CRC rate in a large cohort of adults with newly implanted ITB pump systems with polymer reinforced silicone catheters. Materials and Methods: This is a retrospective study of a prospectively maintained database consisting of patients who had undergone implantation of ITB pump systems with Ascenda (Medtronic, Minneapolis) catheters from 2013 to 2020. Over this seven‐year period, 141 patients underwent ITB pump system implantations; 126 of which had a minimum of one‐year follow‐up. Results: The 126 patients with a minimum of one year follow‐up (average 43 month; range 12–89), had an average age of 51 years (63% male). Severe spasticity was due to spinal cord injury (38%), traumatic brain injury (15%), cerebral palsy (13%), multiple sclerosis (11%), stroke (10%), and other (13%). Nine (7.1%) CRCs occurred in 7 (5.6%) patients (median 6 mo. post‐implant): 5 intrathecal catheter occlusions (range 3–52 months post‐implant), two fractures in one patient (6 months), one disconnection at the catheter pump interface (2 months), and one due to kinking at 84 months No migrations occurred. Conclusions: Reported CRCs have been high for ITB pump systems. Ours is the first large cohort, long‐term study of CRCs related to reinforced catheters; additionally, our low CRC rate compares favorably to previously published data. Thus, implantation of reinforced catheters may be associated with a low CRC rate.